Mechanical bearings with tunable compliance after biological role model of blood sinus hairs - Ingaroca Quispe, Jorge Luis (2016)
In follicle sinus complex of sinus hairs, two blood vessels seem to have a prominent function. Up to date, their biological role is unknown, however, hypothesis suggest that they are used as hydraulical bearing for the hair which is used to change the stiffness and compliance of the fixation depending on the application. Because of the size of the structures of interest experiments at the living object to clarify the biological role are not possible so far. Therefore, mechatronic approaches can help to investigate advantages and possibilities of a bearing with tunable compliance. Thus, in the current thesis, it is develop a mathematical modeling, multi-body simulation and a mechatronic demonstrator of a swinging rod in a bearing with tunable compliance. The tunable compliance of the system was inspired of Jack Spring principle of work, which change the compliance by decreasing the number of active coils.